A project Feasibility Study on the Introduction of Bottled Iodinated Water in the Philippines - Pinili, Dominic M. (College of Engineering, 2001)
I2O Iodinated Drinking Water represents the latest innovation in bottled water products. Using odorless and tasteless Potassium Iodate (KIO3) as fortificant, I2O Iodinated Drinking Water's competitive advantage over its potential industry competitors lies in its capability to supplement the population, with the special mention of those with Iodine Deficiency Disorders or IDD, with the right amounts of Iodine meeting the Recommended Daily Allowance (RDA) regulated by the Department of Health (DOH). As a pioneer product aspiring to make it big in the booming bottled water industry, I2O Iodinated Drinking Water would demand a thorough feasibility study tackling its market, technical, financial, and social aspects to determine its success. As such, the proponents of this study would like to present a summary of the results of this study. Initially, a marketing study was conducted to establish the existence of a bottled water market, whether unmet or unrealized, ready to be satisfied to investigate on the state of its supply thus justifying the introduction of this new product. From this inquiry, it was found out that age 15 and above belonging to income groups C to F (income of Php 100 000) up comprise a target market demanding an unsatisfied 13.22 million liters of bottled water over a projected period of approximately 4 ½ years. A substantial market was thus identified. A Php 3.3 M print-and-TV promotional and information campaign spearheaded by an initial Php 2.2 M budget on the first year was proposed to facilitate marketing activities and ensure its marketability. The results of the marketing study prompted for a continued investigation into its technological viability to determine technical and operational requirements. For the water treatment process, a Reverse Osmosis process utilizing equipment from Rejan Technology Inc. was found to produce the best tasting and odor-free drinking water at the least cost. This shall be complemented by manual bottle filling operation. Both shall utilize a total of 44 workers running a two-shift, 16-hour per day, 6 days-a-week production schedule. A lean production organization under the management and control of a partnership shall exist. The technical study revealed a relatively capital-intensive project. An awareness of all the costs involved is thus required to locate the required funding and assess its profitability. Due to the nature of the business entity and the scale of its operations, it was concluded that the partnership could supply a working capital of approximately Php 2.9 M and provide for the necessary funding required for the total project cost tantamount to Php 4.4 M. From the estimates of all the costs incurred, a balance sheet, pro-forma income statement, and cash flow statement was generated covering the entire five-year projected period. These statements revealed promising financial ratios. Notable among these are the Average Rate of Return of 45% an expected Payback Period of 10.17 months, and an IRR of 71.46%, all revealing an acceptable and profitable project. The project study was concluded with the establishment of its social attractiveness and its implication on health, the economy and the community.